Influence of fertilization on coffee trees vegetative growth in west south Amazon - Dubberstein, Danielly; Partelli, Fabio Luiz; Dias, Jairo Rafael Machado; Espindula, Marcelo Curitiba (Coffee Science - ISSN 1984-3909, 2017)
The standard of knowledge of coffee growth is fundamental to assist in the management of crop, due to the growth of seasonal occurrence throughout the year. The objective was to evaluate the vegetative branches growth of coffee located in South Western Amazon in fertilized and unfertilized plants. The trial was carried out in clonal tillage in a randomized block design with three replicates in time split plot. The main plots were fertilized and unfertilized plants and subplots accommodated the evaluation times (measurements). Evaluations of orthotropic and plagiotropic branches growth and were measured every 14 days, from May 2013 to June 2014, as it was estimated daily rate of vegetative growth. Data were submitted to analysis of variance and means were compared by Tukey test. Fertilization provided higher growth to orthotropic and plagiotropic branches during the period from October to December. Seasonal variations in growth are ascertained along the year, with the highest rates focusing mid-September to early April, when there is bulk of the rainfall in the region. For efficient nutrient management, it is recommended special attention the installment payment of fertilization in this period.